Spinal cord compression secondary to extramedullary hematopoiesis: A rareness in a young adult with thalassemia major - Fareed, Shehab; Soliman, Ashraf T.; De Sanctis, Vincenzo; Kohla, Samah; Soliman, Dina; Khirfan, Diala; Tambuerello, Adriana; Talaat, Mohamed; Nashwan, Abdulqadir; Caparrotti, Palmira; Yassin, Mohamed A. (Acta Biomedica Atenei Parmensis, 2017)
We report a case of a thalassemia major male patient with back pain associated to severe weakness in lower extremities resulting in the ability to ambulate only with assistance. An urgent magnetic resonance imaging (MRI) of thoracic and lumbosacral spine was requested. A posterior intraspinal extradural mass lesion compressing the spinal cord at the level of thoracic T5-8 was present, suggesting an extramedullary hematopoietic centre, compressing the spinal cord. He was treated successfully with thalassemia major alone. The patient was treated with blood transfusion, dexamethasone, morphine and paracetamol, followed by radiotherapy in 10 fractions to the spine (daily fraction of 2Gy from T3 to T9, total dose 20 Gy). His pain and neurologic examination quickly improved. A new MRI of the spine, one week after radiotherapy, showed an improvement of the extramedullary hematopoietic mass compression. In conclusion, EMH should be considered in every patient with ineffective erythropoiesis and spinal cord symptoms. MRI is the most effective method of demonstrating EMH. The rapid recognition and treatment can dramatically alleviate symptoms. There is still considerable controversy regarding indications, benefits, and risks of each of modality of treatment due to the infrequency of this disorder.